The Influence of Rice Types and Boiling Time on Glycemic Index: An In Vivo Evaluation Using the ISO 2010 Method - Anna Vîrlan; Lidia Coșciug; Dinu Țurcanu; Rodica Siminiuc (Foods)
Effective blood glucose management is essential for individuals with type 1 diabetes, particularly when dietary adjustments involve staple foods like rice. As a primary carbohydrate worldwide, rice significantly influences the glycemic index (GI) based on its type and cooking method. This study investigated the impact of rice type and boiling duration on the GI in healthy adults using an in vivo approach aligned with ISO 2010 standards. The glycemic response to four rice types (white round-grain, parboiled medium-grain, white long-grain, and whole-grain long-grain) was measured through postprandial blood glucose levels under both standard and extended boiling conditions to assess their implications for dietary glycemic control. Ten healthy participants (mean age 25 years, body mass index (BMI) 23.0 ± 1.6 kg/m2) consumed rice samples containing 50 g of available carbohydrates, prepared under controlled boiling conditions. Postprandial glycemic response was measured at regular intervals over 2 h following ingestion, with glucose solution as a reference food. The GI was calculated based on the incremental area under the glycemic response curve for each rice sample. Extended boiling significantly increased the GI across all rice types. White round-grain rice exhibited the highest relative increase (+15.8%) in the GI, while whole-grain long-grain rice, despite showing a greater percentage increase (+25.4%), maintained the lowest overall GI due to its high amylose and fiber content. Rice types with higher amylopectin content demonstrated faster glycemic responses and higher GI compared to high-amylose types. This study highlights rice type and cooking time as critical factors influencing postprandial glycemic response. Shorter boiling durations may benefit individuals requiring strict glycemic control, particularly those with diabetes, underscoring the importance of personalized dietary guidance for managing glycemic outcomes effectively.